2002
DOI: 10.3168/jds.s0022-0302(02)74313-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Milk Replacer Once Versus Twice Daily on Glucose Metabolism in Holstein and Jersey Calves

Abstract: Eighteen Holstein (experiment 1) and 15 Jersey (experiment 2) heifer calves were fed milk replacer once or twice daily to determine effects of feeding frequency on weight gain, starter intake, and glucose metabolism. Body weights were measured weekly from birth to 8 wk. Blood samples were collected at wk 1 through 6 from all calves before and at 30, 60, 90, 120 and 180 min after the morning feeding. Plasma was analyzed for glucose, insulin, glucagon, and nonesterified fatty acids (NEFA). Urine was collected 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 16 publications
(32 reference statements)
9
53
3
Order By: Relevance
“…Error bars represent SEM. Calculated parameters and statistics are given in Table 3. 7 ment with previous studies performed on young calves (Stanley et al, 2002;Bach et al, 2013;Yunta et al, 2015). This is, however, the first study in which this decrease has been assessed and compared in calves that were maintained on MR and calves that were progressively weaned during their first 3 mo of life, indicating that the decrease in sensitivity is independent of feeding strategy.…”
Section: Decrease In Insulin Sensitivitymentioning
confidence: 50%
See 1 more Smart Citation
“…Error bars represent SEM. Calculated parameters and statistics are given in Table 3. 7 ment with previous studies performed on young calves (Stanley et al, 2002;Bach et al, 2013;Yunta et al, 2015). This is, however, the first study in which this decrease has been assessed and compared in calves that were maintained on MR and calves that were progressively weaned during their first 3 mo of life, indicating that the decrease in sensitivity is independent of feeding strategy.…”
Section: Decrease In Insulin Sensitivitymentioning
confidence: 50%
“…More interestingly, that study also showed that calves at ~14 wk of age are already relatively insensitive to insulin, compared with healthy nonruminants (Caumo et al, 2000;Stefanovski et al, 2011). Another study revealed that insulin sensitivity in neonatal dairy calves (<6 wk of age) decreases from wk 3 to 6, when calves are gradually weaned (Stanley et al, 2002). Moreover, Bach et al (2013) reported that a greater level of MR allowance (8 vs. 4 L/d) had a negative effect on the development of insulin sensitivity in young calves (1-8 wk of age) with ad libitum access to starter feed.…”
Section: Introductionmentioning
confidence: 86%
“…These were accordant with the results of growth performance, digestibility trial and meat chemical composition in the Liuyang black castrated goats. The urea concentration in the serum reflects the metabolic balance between the protein and amino acids (Stanley et al., ). In this study, there was a significant decrease for urea in the ramie hay treatment than that of ramie silage treatment, which showed that the ramie hay treatment was better for promoting protein synthesis and deposition than ramie silage treatment in the body of Liuyang black castrated goats.…”
Section: Discussionmentioning
confidence: 99%
“…Increased insulin secretion compensates partially for decreased tissue response to insulin and has been observed in Thoroughbreds, calves and humans (Hoffman et al 2003, Stanley et al 2002, Welch et al 1990). However, insulin is also an important hormone in regulating fat metabolism, growth, and vascular function.…”
Section: K Treiber Et Almentioning
confidence: 99%